2011
DOI: 10.2169/internalmedicine.50.5771
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of Carpal Tunnel Syndrome: Clinical Significance and Limitations in Elderly Patients

Abstract: Objective Carpal tunnel syndrome (CTS) severity increases with age. Ultrasonographic measurement of the median nerve cross-sectional area (CSA) is an additional or complementary method for CTS diagnosis. The present study was aimed to investigate the diagnostic significance of median nerve CSA in various age groups of CTS patients. Methods The subjects were patients with electrophysiologically confirmed CTS and age-matched controls. Sonographic measurements of the median nerve CSA were performed. Results A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…It is suggested that results of NCS indicating severe disease could be related to delayed treatment owing to age-related reduced pain sensitivity because of reduced nerve membrane excitability 21) . Reportedly, the CSA of the median nerve was correlated with distal motor and sensory latencies of the median nerve and severity of CTS except in patients aged >80 years in whom CSA was not m regardless of severe CTS 13) . Our study demonstrated that Group I patients showed higher NCS grades and USG proven more severe median nerve swelling.…”
Section: Discussionmentioning
confidence: 93%
“…It is suggested that results of NCS indicating severe disease could be related to delayed treatment owing to age-related reduced pain sensitivity because of reduced nerve membrane excitability 21) . Reportedly, the CSA of the median nerve was correlated with distal motor and sensory latencies of the median nerve and severity of CTS except in patients aged >80 years in whom CSA was not m regardless of severe CTS 13) . Our study demonstrated that Group I patients showed higher NCS grades and USG proven more severe median nerve swelling.…”
Section: Discussionmentioning
confidence: 93%
“…although at least 1 study showed that the CSA of the median nerve at the wrist exceeded the upper limit of normal for the majority of tested patients with severe CTS [47]. This dissociation between increased CSA and FMMW severity encountered in patients with chronically severe CTS may be particularly evident in elderly individuals [49].…”
Section: Discussionmentioning
confidence: 95%
“…Nichtsdestotrotz und nicht zuletzt aufgrund individuell unterschiedlicher Nervendicken, Geschlechts- [46], Seiten- [47] und Altersunterschiede [48,49] Hobson-Webb u. Mitarb. konnten für einen Verhältniswert zwischen der Nervenquerschnittfläche auf Handgelenkhöhe und einer Schnittebene 12 cm proximal der Raszetta von ≥ 1,4 eine Sensitivität von 100 % nachweisen [36].…”
Section: Nervenquerschnittfläche (Raszetta)unclassified